The comparison of mesh and sutured repair for adult umbilical hernia: a prospective study - Agarwal, Shwetank; Kumar, Ajay (International Surgery Journal, 2018)
Background: Umbilical hernia is the commonest of all the abdominal hernias. The current study was planned to evaluate the outcome of Mayo’s tension free mesh repair to sutured repair in umbilical hernias. Methods: The prospective study was piloted on 110 patients who underwent umbilical hernia repair over a period of 1-year period in the department of General Surgery. The patients were divided into two groups – Group A comprises 68 patients and group 2 consists of 42 patients in which suturing, and mesh repair was done respectively. The patients were then grouped in Suture group or Mesh group as per the procedure done and 1 year follow up was done. The complications and the duration of hospital stay in both groups was recorded. Results: The mean age of the subjects was 52.8±12.1 years. The ratio of male to female was 7:4. Seven patients (10.3%) developed recurrence following sutured repair compared to none following mesh repair (P<0.05). Five patients (5.3%) developed wound infection following suture repair compared to none in the mesh group (P<0.05). Two patients had hematoma while 1 had seroma in suture group, both haematomas occurred in patients who underwent the Mayo repair. Conclusions: According to present results mesh repair is the preferred technique of manoeuvre in umbilical hernias. Mesh repair for umbilical hernias is in effect and concomitant with negligible morbidity.